Pengaruh Rekrutmen, Pengembangan Karir dan Kompensasi Terhadap Kinerja Pegawai di Dinas Pendidikan dan Kebudayaan di Kota Probolinggo - Agustin, Sentiana; Yatiningrum, Agung; Hermawan, Dedi Joko (JUMAD : Journal Management, Accounting, & Digital Business, 2024)
This research was conducted on the Department of Education and Culture in the City of Probolinggo with the aim of finding out the significant influence of Recruitment, Career Development and Compensation simultaneously on Performance at the Department of Education and Culture in the City of Probolinggo. The independent variables in this research are Recruitment, Career Development and Compensation. Meanwhile, the dependent variable is Employee Performance. The type of research used is quantitative research with a causal associative approach. Data collection techniques include interviews, questionnaires and documentation. The population referred to in this research is all employees at the Probolinggo City Education and Culture Office. Sample determination was carried out using non-probability sampling which resulted in a sample of 60 respondents. This research data uses primary and secondary data. The data analysis techniques used are validity test, reliability test, classical assumption test, multiple regression analysis, coefficient of determination analysis and hypothesis testing. The results of the research show that Recruitment has a significant effect on Employee Performance, Career Development has a significant effect on Performance. Compensation has a significant effect on Employee Performance.